TELAAH DEKONSTRUKSI KEKUASAAN DALAM NOVEL DARI FONTENAY KE MAGALLIANES KARYA NH. DINI DALAM PERSPEKTIF BUDAYA - -, Sugiarti (Diksi, 2015)
This article concerns a study whose objective is to explain several issues related to (1) a description of the domination, hegemony, and subordination of characters in a novel, (2) the function of the power culture experienced by the characters, and (3) the meaning of power deconstruction in the novel. To reach the objective, the researcher conducting the study employs a qualitative-descriptive method. The source of data is the novel Dari Fontenay ke Magallianes by Nh. Dini. The data are in the form of extracts taken from the novel and, complemented with the researcher's thoughts pertaining to issues related to society and power, collected through documentation and literary study with thorough understanding. Data validity is confirmed by employing a series of such techniques as (1) careful observation, (2) adequate literary reference, (3) peer discussion among parties sharing interest in literary works, and (4) triangulation by searching available articles for related information about the novelist concerned. The results of the study show the following. (1) The types of power described in the novel are greatly reflected in the behavior of a character's husband toward his family (wife and children) and his colleagues. The power types could be exposed through the husband's attitude, ideology, and behavior in response to the surrounding environment as part of his community. (2) The power culture functions to provide some characters with experiences suggesting that some social issues have to be overcome by way of different unsatisfactory treatments. In addition, the power functions as a "bond" that makes someone obey what is instructed by the one who is in power. (3) An analysis on the meaning of the power manifested in the text through female characters shows that it is a kind of counterdiscourse against the hegemony of the central power. Keywords: current thought movement, new perspective